Evaluation of increase in overturning tendency of elevated water tanks under earthquake induced P-Δ effects - Chowdhury, Pronoy Roy (Journal of Structural Engineering, 2025)
P-Δ effect plays a crucial role to trigger an early failure of high-rise structures under seismic ground motions. This effect may further be aggravated for structures like elevated tanks having a large mass concentrated at the top slender supporting structure. The study attempts to visualize impact of P-Δ effect on elevated tanks subjected to seismic loading. Inverted pendulum structures develop increased tendency to topple down in the inelastic range of forces. The paper attempts to evaluate earthquake induced P-Δ effect, which is time progressive in nature and hence geometrical non linearity is also increased over each of the time steps. Under each yield excursion, especially for R.C members, the hysteretic behaviour further contributes to lateral drift due to stiffness degradation of the frame elements. A realistic example tank with frame type of staging considering fixed base has being studied for El-Centro and Spectrum consistent ground motion, for four types of hysteretic behaviour namely (i) Purely Elasto-Plastic Behaviour (ii) Strength Degrading Behaviour (iii) Stiffness Degrading Behaviour and (iv) Strength and Stiffness degrading behaviour. From the study it is found that interpretation of the proper response reduction factor value (Rμ) may serve as a useful input for performance based seismic design of elevated tanks.